The influence of spironolactone on the serum electrolytes balance and renal cortical magnesium and calcium contents in cisplatin – treated rabbits - Abdel-Gayoum, Abdelgayoum A.; Ahmida, Mohamed H. S. (Asian Journal of Medical Sciences, 2018)
Background: Cisplatin is a widely used anticancer drug. Its use is known to induce nephrotoxicity and may be associated with disturbance of the electrolyte balance. Spironolactone, an antagonist of aldosterone, is frequently prescribed as a potassium sparing diuretic. Aims and Objective: The present study aims to investigate whether spironolactone can correct the cisplatin-induced electrolyte disturbance in the rabbit. Materials and Methods: Thirty two New Zealand rabbits were distributed into four groups. Animals of control (C); spironolactone (S); cisplatin (P); spironolactone and cisplatin (SP) groups were injected ip with saline; given spironolactone (20 mg/kg bw/day) orally for 5 days; injected ip with cisplatin (6.5 mg/kg bw); given both spironolactone and cisplatin, respectively. Serum, liver and kidney cortical homogenates were used for biochemical analysis. Results: Serum creatinine and urea levels of P were significantly (P<0.001) elevated and were severely raised in SP by 7-fold and 2.7-fold. The serum magnesium was increased in S and SP groups by 93.75% and 112%, respectively and was depressed in P by 18.75% compared to C. Serum potassium and calcium of P were significantly (P<0.001) depressed, whereas, serum calcium levels in the S and SP were significantly elevated. The liver magnesium and calcium of SP were elevated by 38.37% and 40.7%, respectively, whereas, kidney magnesium showed reduction in the S, P and SP by 36%, 24% and 19%, respectively and elevated in the SP group by 26.56% compared to S group. The kidney calcium was depressed in the S, P and SP by 30.89%, 40.0% and 28.2%, respectively compared to C. Conclusion: Cisplatin treatment depleted the serum and renal cortical magnesium. The serum calcium and potassium were reduced secondary to the magnesium depletion. The co-administration of spironolactone reversed the cisplatin-induced magnesium and calcium depletions in serum and renal tissue. Asian Journal of Medical Sciences Vol.9(3) 2018 10-16